Conformational preferences of hypermodified nucleoside lysidine (k(2)C) occurring at wobble position in anticodon loop of tRNA(IIe) - Sonawane, Kailas D.; Tewari, Ravindra (Nucleosides Nucleotides & Nucleic Acids, 2008)
Conformational preferences of hypermodified nucleoside, 4-amino-2-(N(6)-lysino)-1-(beta-D-ribofuranosyl) pyrimidinium (Lysidine or 2-lysyl cytidine), usually designated as k(2)C, have been investigated theoretically by the quantum chemical perturbative configuration interaction with localized orbitals (PCILO) method. The zwitterionic, non-zwitterionic, neutral, and tautomeric forms have been studied. Automated geometry optimization using molecular mechanics force field (MMFF), semi-empirical quantum chemical PM3, and ab initio molecular orbital Hartree-Fock SCF quantum mechanical calculations have also been made to compare the salient features. The predicted most stable conformations of zwitterionic, non-zwitterionic, neutral, and tautomeric form are such that in each of these molecules the orientation of lysidine moiety (R) is trans to the N(1) of cytidine. The preferred base orientation is anti (chi = 3 degrees) and the lysine substituent folds back toward the ribose ring. This results in hydrogen bonding between the carboxyl oxygen O(12a) of lysine moiety and the 2'-hydroxyl group of ribose sugar. In all these four forms of lysidine O(12a)...H-C(9) and O(12b)...H-N(11) interactions provide stability to respective stable conformers. Watson-Crick base pairing of lysidine with A is feasible only with the tautomeric form of usual anti oriented lysidine. This can help in recognition of AUA codon besides in avoiding misrecognition of AUG.
Keywords: hypermodified; k(2)C; lysidine; stable conformers